Pengaruh Celebrity Endorser, Kualitas Produk dan Harga Terhadap Keputusan Pembelian Scarlett Whitening Body Lotion di Jabodetabek - Paskariyani, Hana; Nurmahdi, Adi (Peneliti.net, 2025)
This study aims to examine and analyze the influence of celebrity endorsers, product quality, and price on purchasing decisions for Scarlett Whitening Body Lotion in Jabodetabek. This study uses an associative causality research method. The population in this study consists of all consumers who use Scarlett Whitening Body Lotion in the Jabodetabek area. The sampling technique used is nonprobability sampling. The sample size used in this study was 125 respondents. Data was analyzed using SmartPLS 4.0. The results of this study show that a celebrity endorser has a not positive and insignificant influence on purchasing decisions. Product quality has a positive and significant influence on purchasing decisions. Price has a positive and significant influence on purchasing decisions.